Role Of ψ-Operator in the Study of Minimal Open Sets - MIAH, C.; MODAK, S.; ISLAM, MD. M. (Iraqi Journal of Science, 2023)
The operator ψ has been introduced as an associated set-valued set function. Although it has importance for the study of minimal open sets as well as minimal I-open sets. As a result of this study, we introduce minimal I^*-open sets . In this study, several characterizations of minimal I^*-open sets are also investigated. This study also discusses the role of minimal I^*-open sets in the *-locally finite spaces. In an aspect of topological invariant, the homeomorphic images of minimal I^*-open set has been discussed here.